Tradisi Nunas Paice di Desa Adat Panji Sebagai Praktik Bhakti dan Solidaritas Komunal - Gusti Putu Kondita; I Made Sedana; Ida Bagus Wika Krishna (Kamaya: Jurnal Ilmu Agama, 2026)
The nunas paice tradition in Desa Adat Panji, Sukasada District, Buleleng Regency, is a Balinese Hindu ritual practice that reflects the relationship between devotion, sacred grace, local dresta, and communal participation. This article aims to interpret the theological, symbolic, and socio-cultural meanings of nunas paice as both a practice of bhakti and a form of communal solidarity among Balinese Hindus. This study employs an interpretive qualitative approach through documentation study and library research. The data were collected from public documents on Desa Adat Panji, reports on piodalan ceremonies at Pura Bukit/Pura Subak Gede Tiing Tali, customary-legal documents of Desa Adat Panji, and recent studies on Balinese Hindu rituals. The analysis was conducted through data reduction, thematic categorization, source triangulation, and symbolic interpretation, supported by interpretive anthropology, ritual theory, social construction theory, and the Tri Hita Karana perspective. The findings show that nunas paice should not be understood merely as the act of receiving ritual food or ceremonial offerings. Rather, it functions as a micro-religious practice through which the community interprets divine grace, sacred symbols, and social togetherness. The novelty of this article lies in its interpretation of nunas paice as a space of communal religiosity that integrates theological awareness, symbolic acceptance of sacred blessing, and the reproduction of social solidarity through collective ritual participation. This article concludes that nunas paice represents a form of Balinese Hindu local wisdom embodied in everyday practice and contributes to maintaining the balance of parahyangan, pawongan, and palemahan within communal religious life.